Transformation of the Archipelago: The Journey of Islam and its Legacy in Indonesian Culture - Aninda Tri Safinatun Najah (Criksetra: Jurnal Pendidikan Sejarah, 2025)
This research examines the influence of Islamic civilization on the formation of civilization and social life in Indonesia. The main focus is on understanding how the arrival and interaction of Muslim traders from Arabia, Persia, and India affected the social, cultural, and religious development in Indonesia. The aim of this research is to historically analyze the role of Islamic civilization in shaping the national identity and social dynamics of Indonesia. This study employs the library research method to explore the history of the spread of Islam in Indonesia. The findings indicate that Islamic civilization has significantly contributed to shaping the social and cultural values of Indonesian society, particularly in aspects such as education, law, art, and traditions. Furthermore, the research reveals that the spread of Islam through trade routes created strong social and economic networks in the archipelago, which contributed to the integration and unity of the Indonesian territory. The conclusion of this research is that Islamic civilization played a role in the dissemination of religion and in forming social and cultural foundations that are still evident today. This influence is reflected in the daily lives of Indonesian people, both in religious practices and in the social values they uphold. Therefore, understanding the role of Islamic civilization in Indonesia's history provides important insights into the development of national identity and cultural diversity.